Cellobiose dehydrogenase from Phanerochaete chrysosporium is encoded by two allelic variants. - Li, B (1997)
The complete nucleotide sequences of two alleles of cellobiose dehydrogenase, cdh-1 (3,627 bp) and cdh-2 (3,623 bp), from Phanerochaete chrysosporium OGC101 are reported. The nucleotide sequences of cdh-1 and cdh-2 exhibit 97% similarity. A total of eighty-six point mutations between cdh-1 and cdh-2 are observed. Both alleles have 14 exons, and the introns are located at exactly the same positions. The translation products of these alleles have identical amino acid sequences. Restriction fragment length polymorphism analyses of homokaryotic derivatives show segregation of the CDH alleles.